2012
DOI: 10.12934/jkpmhn.2012.21.1.79
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Standardized Patients in Psychiatric Nursing Practical Training for Nursing College Students

Abstract: Purpose: This study was done to examine the effects of using standardized patients in psychiatric nursing practical training for nursing college students. Methods: This research design was a quasi-experimental pre-and-post-test control and experimental group methodological comparison study. Forty-four (Exp.=23, Cont.=21) nursing college students in G city participated in the study. The experimental group received psychiatric nursing practical training using standardized patients, and the control group received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 20 publications
(12 reference statements)
4
22
0
1
Order By: Relevance
“…A higher score indicates a higher level of communication efficacy. Cronbach's ⍺ was .57 at the time of development, and .95 in the study by Park and Kweon [18]. Cronbach's ⍺ was .92 in this research.…”
Section: ) Communication Efficacysupporting
confidence: 54%
See 2 more Smart Citations
“…A higher score indicates a higher level of communication efficacy. Cronbach's ⍺ was .57 at the time of development, and .95 in the study by Park and Kweon [18]. Cronbach's ⍺ was .92 in this research.…”
Section: ) Communication Efficacysupporting
confidence: 54%
“…The results of this study were comparable to those of previous studies by Ayres [17], who reported enhancement of learning efficacy in nurses and nursing students after communication education. Those studies [17,18] applied a small team-based approach, and students were provided with opportunities to explore solutions for given cases in cooperation with team members, and to make corrections through team discussion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when providing active training, nursing students' attitudes were very different. Nursing students practiced simulation training with standardized patient before psychiatric practice; they increased learning satisfaction and self-efficacy, as well as anxiety reduced (Park & Kweon, 2012). Perhaps the solution of this problem needs innovative and active methods; many educators may have persisted typical education method.…”
Section: Resultsmentioning
confidence: 99%
“…Having a fear of psychiatric practice is a result of negative social attitudes (Park & Kweon, 2012). These negative attitudes towards psychiatry are factors that prevent nursing students from practicing comfortably (Happell & Hayman-White, 2009).…”
mentioning
confidence: 99%